Implementation of an enhanced recovery after surgery (ERAS) protocol in a gynaecology department – the follow-up at 1 year - Nikodemski, Tomasz; Biskup, Agnieszka; Taszarek, Aleksandra; Albin, Małgorzata; Chudecka-Głaz, Anita; Cymbaluk-Płoska, Aneta; Menkiszak, Janusz (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : An ERAS protocol provides the latest perioperative care principles, whose primary aim is to reduce complication rates, and therefore mortality. The aim of this study is to establish the progress of the ERAS pathway implementation in our gynaecology department. Material and methods : This was a retrospective analysis of two sets of 100 consecutive medical records: patients treated before (PRE-ERAS) and after (ERAS) introduction of the ERAS protocol. All patients were comparable and all underwent major gynaecological surgery. Patients as well as medical and nursing staff were informed about the proposed preparation, surgical management and postoperative routine. Results and conclusions : Patients were given supper and drank water during the night. Laparoscopic surgery was used in 44% and spinal anaesthesia was given for open surgery in 43 study patients. Use of drains was reduced only by 23%, bowel preparation by 15%. Intravenous fluid administration was reduced by 22%. Use of postoperative morphine was minimised to 12 patients. Postoperative nausea was managed with the regular use of anti-emetics. Anti-coagulation was given to 80% of the study group. Difficulties in the introduction of the ERAS protocol were due to refusal by some patients to mobilise and eat early postoperatively. Patients in the ERAS programme group were discharged earlier. Further information about the ERAS protocol in the media would facilitate patients’ education among conservative society. In order to introduce new and innovative treatment methods, one has to take into account the cultural and ideological factors, especially when patient involvement is essential.